2014
DOI: 10.1007/s00221-014-3977-y
|View full text |Cite|
|
Sign up to set email alerts
|

Infusion of growth hormone into the hippocampus induces molecular and behavioral responses in mice

Abstract: Growth hormone (GH) has been implicated in a variety of brain functions, including neural development, cognition, and neuroprotection. The biological effects of GH are known to rely on the binding of GH to the GH receptor (GHR), yet the resulting signals in the brain remain poorly understood. The present study investigated the effects of hippocampal infusions of recombinant GH and a GHR antagonist on the expression of immediate early genes (IEGs) and behavioral responses in mice. The infusions induced differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…However, these positive effects of GH have been widely demonstrated in different experimental animal models [29,30,31,32,33]; even in old animals, in which the cognitive impairment of hippocampal-dependent functions, such as learning and memory, is associated with a decrease in the secretion of GH and IGF-I, as in our species [4,17,18,32]. …”
Section: Discussionmentioning
confidence: 99%
“…However, these positive effects of GH have been widely demonstrated in different experimental animal models [29,30,31,32,33]; even in old animals, in which the cognitive impairment of hippocampal-dependent functions, such as learning and memory, is associated with a decrease in the secretion of GH and IGF-I, as in our species [4,17,18,32]. …”
Section: Discussionmentioning
confidence: 99%
“…Neuronal Npas4 mRNA expression had been linked previously to stimulation by growth factors (45,58), although this may not translate to changes at the protein level (29). Specifically, Ooe et al (45) have reported that Npas4 expression downstream of NGF stimulation was dependent on PI3K/Akt.…”
Section: Npas4 Is Regulated By Calcium and Prevents Beta Cell Deathmentioning
confidence: 99%
“…In addition, GH deficiency has been linked with cognitive impairment [ 16 , 35 , 37 ], and previous research has shown that Gh expression increases in the rat hippocampus following repeated learning in response to eye-blink conditioning [ 38 ]. In mice, infusion of GH into the hippocampus changes expression of immediate early genes and induces spontaneous locomotion, grooming, and anxiety-like behavior [ 39 ]. Consistent with observations in rat, our data in mice show that Gh is expressed in the hippocampus in a hormone-dependent manner; this may be an important aspect of learning and memory mediation by Gh .…”
Section: Discussionmentioning
confidence: 99%